USERS’ PERCEPTION ON CHILDREN AT MASJID – PLANNING FOR CHILDREN FRIENDLY MASJID - Abu Bakar, Aniza; Zulkifely, Zur Atiqa; Abd. Majid, Noor Hanita; Ibrahim, Mohd Burhan (PLANNING MALAYSIA, 2019)
Masjid is an important institution to know Allah SWT, empower, and unite society. Early exposure of children to masjid is crucial as nurturing them to love masjid is a process towards loving the creator, strengthening their faith, and improving akhlaq (behaviour) towards becoming a good Muslim and eventually forming a stable society and nation. However, there have been some negative perceptions on the presence of young children in masjid among the jamaah (congregational members). This discourages families in engaging their young children with masjid as early as possible. Eventually, it would hinder them from learning high values of Islam that would strengthen their faith, shape good character, and akhlaq. This study aims to identify the perception of the parents or guardian that bring children to masjid as well as other jamaah on the presence of children at masjid through a structured questionnaire survey with random sampling approach. Eight masjids within the urban area of Kuala Lumpur and Selangor were involved with the target of fifty respondents each. 55.2% of the 400 respondents were parents/guardians that bring children to the masjid. The findings suggest that respondents welcome the presence of children at masjid as it is deemed suitable as a place for children's education and that masjid should provide educational programmes for them. Crying and playing children seem to distract the jamaah. Hence they feel designated spaces for children is deemed necessary.